Mathematical Modelling of Two-axis Photovoltaic System with Improved Efficiency - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY, 2015)
Design of a two axis sun tracking system is much more complex compared to one axis. Tracking the sun could be accomplished by either running algorithms integrated to system or using photoresistances. In this study, mathematical formulation of sun tracking system using photoresistances and its mechanical components, is derived. A new sun tracking system is proposed considering the results of calculation. The system capable of moving in two axis tracks the sun from sunrise to sunset as sunlight is always normal to its surface. So, it profited from sunlight optimally. System stops during cloudy weather or after sunset and so inessential power consumption is prevented. Moreover, consumed energy by the motors providing movement of system is minimized by the new system. Designed two axis sun tracking system is compared with a fixed system and it is observed that 30 % more electrical energy is produced annually.
Keywords: Two axis tracking; solar energy; sun tracking